AGROWISATA NANAS DESA MADU SARI KABUPATEN KUBU RAYA - Fannisaningrum, Rahmi; Alhamdani, Muhammad Ridha; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Madu Sari Village is a village in Sungai Raya District that has a large area of land in the form of peat, with the potential to become a village that produces horticultural commodities. Madu Sari Village can supply ±600 pineapples per week when it is not in season and ±2,000 pineapples per week when it is in season. This village can be further developed to become an agrotourism destination. The formulation of the problem for this final assignment is